Description Of Duplication Of Medical Record Numbers In Outpatient Registration At RSU Madani Medan In 2021 - Abdul Malik Ritonga; Sarida Surya Manurung; Dinda Dinda; Jonni Sastra Manurung (Jurnal Media Informatika, 2023)
Good medical record number numbering is one of the keys to the success or goodness of medical record management of a health service, of course, if supported by a good system. Quality human resources and good procedures or work procedures as well as adequate facilities or facilities. The special purpose is to identify the policy of the medical record numbering system, identify the factors causing the duplication of medical record numbers. One patient file is accompanied by one medical record number. The purpose of medical record numbering is to distinguish one patient's medical record from another, but in Madani Hospital there are still duplications of patient medical record numbers that can cause health services to be disrupted and the patient's disease history is not well documented, this study aims to determine the number of duplicated medical record numbers at Madani Hospital. This research uses a type of descriptive research, namely research.